Tracking anthropogenic sources in a small catchment using Zn-isotope signatures. (December 2020) - Desaulty, Anne-Marie; Perret, Sébastien; Maubec, Nicolas; Négrel, Philippe
Abstract: Tracking metal pollution in surface water is a major environmental, public-health and economic issue. Knowledge of the behaviour of metals such as zinc (Zn), in stream sediments and water, is a key factor to improving river water quality. Because the isotopic compositions of Zn can be used as an environmental tracer for tracking the sources of man-made materials and its transport into water and soil, we have used Zn isotopes for studying the anthropogenic impact on a watershed. As a case study, we chose a small watershed in the Loire River basin, near Orléans (France). The Egoutier spring issues in a pristine area, but its water is affected a few kilometres downstream by liquid effluents from a wastewater treatment plant (WWTP) and farther down still by diffuse pollution from road traffic. We sampled the liquid effluents as well as water and sediments along an upstream to downstream transect. For liquid samples, we took "grab" samples and integrated samples using passive DGT (Diffusive Gradients in Thin films) samplers. The advantages of DGT are (1) to pre-concentrate in-situ the Zn dissolved in water—avoiding a time-consuming chemical preparation—and (2) to integrate the potential variations of Zn isotopic signature over time. The mobile fraction of sediments—that released by the leaching in 0.2N HCl—was also investigated. The δ 66/64 Zn values in water and sediments along the upstream/downstream profile clearly showed the anthropogenic input of WWTP effluents in the river, which was still visible several kilometres downstream in water. This dissolved anthropogenic contribution is easily transported along the transect and only slightly fixed by adsorption on sediments, probably due to their low clay-mineral content. For the farthest downstream sample, affected by road traffic, the pollution source is difficult to discern due to the similar δ 66/64 Zn values in WWTP effluents and in road-traffic particles. Here, the use of DGT has proved to be a major asset: during a rainfall event, road traffic particles were leached by rainwater, forming runoff with a relatively high Zn content that flowed into the river, and DGT monitoring showed it to be an adequate method for discerning discontinuous anthropogenic input into the river water. Graphical abstract: Image 1 Highlights: Though Zn is essential for life, in excess amounts it may be toxic to organisms. We used δ 66/64 Zn for tracking the WWTP and road-traffic emissions in a small river. DGT is a major asset to record δ 66/64 Zn of discontinuous anthropogenic emissions.